Pterional Approach - Luzzi, Sabino; Giotta Lucifero, Alice; Bruno, Nunzio; Baldoncini , Matias; Campero, Alvaro; Galzio, Renato (Acta Biomedica Atenei Parmensis, 2022)
The pterional approach is a workhorse in neurosurgery, to the point where perfect knowledge of its execution is essential in neurosurgical daily practice. The pterional transsylvian corridor is used to treat aneurysms involving anterior circulation, basilar apex, the proximal segment of the superior cerebellar and posterior cerebral artery, arteriovenous malformations and cavernous hemangiomas of the basal forebrain, anterior and middle skull base tumors, gliomas of the frontal, parietal, and temporal opercula, insula, mediobasal temporal region, cerebral peduncles, interpeduncular fossa, and also orbital lesions. We herein overview the core technique and variations of the pterional approach aimed at broadening surgical freedom and decreasing the risk of approach-related complications.